Theology in a suffering world: glory and longing - Southgate, Christopher (Cambridge University Press, 2018)
In this book, Christopher Southgate proposes a new way of understanding the glory of God in Christian theology, based on glory as sign. Working from the roots of the concept in the Hebrew Bible, Theology in a Suffering World: Glory and Longing shows that 'glory' is not necessarily about beauty or radiance, but is better understood as a sign of the unknowable depths of God. Southgate goes on to show how John and Paul transform the concept of glory in the light of the cross. He then explores where glory may be discerned in the natural world, including in situations of pain and suffering. In turn glory is explored in the poetry of R. S. Thomas and the writings of the Jewish mystic Etty Hillesum. Finally, the book considers what it might mean for Christians to be 'transformed from one degree of glory to another': that might mean becoming a sign of the great sign of God that is Christ, and conforming their longing to God's longing for the Kingdom to come